2021
DOI: 10.3390/en14082319
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Wind Turbine Aging through Operation Data Calibrated by LiDAR Measurement

Abstract: This study analyzed the performance decline of wind turbine with age using the SCADA (Supervisory Control And Data Acquisition) data and the short-term in situ LiDAR (Light Detection and Ranging) measurements taken at the Shinan wind farm located on the coast of Bigeumdo Island in the southwestern sea of South Korea. Existing methods have generally attempted to estimate performance aging through long-term trend analysis of a normalized capacity factor in which wind speed variability is calibrated. However, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…A further SCADA-based study of performance decline with age is given in [13]: LiDAR and SCADA data are employed for the analysis of the behaviour of three Mitsubishi MWT-1000A wind turbines for the first four years of operation and the achieved estimate is an average decline of -0.52% per year, which is higher than the plausible expectations based on the reasoning of [6].…”
Section: Literature Based On Scada Data Analysismentioning
confidence: 99%
“…A further SCADA-based study of performance decline with age is given in [13]: LiDAR and SCADA data are employed for the analysis of the behaviour of three Mitsubishi MWT-1000A wind turbines for the first four years of operation and the achieved estimate is an average decline of -0.52% per year, which is higher than the plausible expectations based on the reasoning of [6].…”
Section: Literature Based On Scada Data Analysismentioning
confidence: 99%
“…In [12] and [13], two fleets of operating similar types of wind turbines are analyzed in order to estimate the variability of the ageing effects and it is observed that trends severe as in [10] regard a minority of the turbines. Further relevant studies about SCADA-based estimations of wind turbine performance decline are [14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…As the effect of power deficits are more prominent from cut-in to rated wind speeds, inclusion of data from this dynamic operating region of the turbine is essential for such analysis. Study by Kim and Kim (2021), based on the SCADA data, uses the turbine's power curve for performance comparison. As discussed in Veena, Mathew and Petra (2020), limitations of manufacturer's power curve in understanding the site specific dynamics of the velocitypower response of the turbines has been well established in several previous studies.…”
Section: Introductionmentioning
confidence: 99%